Cyperus Odoratus l. (Cyperaceae): a Newly Recorded Species in Flora of Upper Gangetic Plain (Fugp), India (Indian Journal of Advanced Botany (IJAB), 2026)
Cyperus odoratus L. (Cyperaceae) is reported here as a new distributional record for the Flora of the Upper Gangetic Plain and the adjacent Siwalik and Sub-Himalayan tracts of Uttar Pradesh, India. The species was encountered during targeted floristic surveys conducted between 2020 and 2025. Identification was confirmed through detailed morphological examination and comparison with authenticated specimens and protologues. This addition expands the known range of the species in northern India and highlights the need for continued taxonomic documentation in understudied transitional zones. This paper provides a detailed taxonomic description, citation, habit, habitat, ecology, flowering and fruiting, distribution, and photographs of the species.